Optimization Of Traffic Management At The Bakauheni Ferry Port, Lampung Province - Chairul Insani Ilham; Yohan Wibisono; Devi Heri Andriyani (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Bakauheni Ferry Port is the gateway to the southern part of Sumatra Island which connects Bakauheni Port (South Lampung) with Merak Port (Banten Province). In its implementation, it is necessary to optimize good crossing traffic management. This study aims to determine the zoning system at the Bakauheni Ferry Port based on the Regulation of the Minister of Transportation concerning Ferry Port Sterilization and the placement of supporting signs along with the traffic flow patterns of passengers and vehicles at the Bakauheni Ferry Port based on the Decree of the Director General of Land Transportation Number SK.242/HK.104 /DRJD/2010. The method used to collect data in this research is observation and problem identification, the data is divided into primary and secondary data, primary data in the form of observations and surveys, while secondary data in the form of institutional and literature. Analysis methods are used to analyze problems such as zoning system analysis, Vehicle Traffic Analysis and Analysis of Directional Signs Equipment. The result is that the lack of application of the zoning system at the Bakauheni Ferry Port causes service users to enter the prohibited zone and carry out activities there and the lack of precise placement of signs supporting the zone system at the Bakauheni Ferry Port. Meanwhile, in the management of vehicle traffic flow patterns at the Bakauheni Ferry Port, it is not in accordance with the Crossing Traffic Management Technical Guidelines.